2005
DOI: 10.5271/sjweh.915
|View full text |Cite
|
Sign up to set email alerts
|

Long workhours, work scheduling and work-related injuries among construction workers in the United States

Abstract: Objectives The objectives of this study were (i) to examine work scheduling in construction and (ii) to establish whether there is any connection between workhours and safety outcomes among construction workers.Methods The National Longitudinal Survey of Youth, 1979 cohort (NLSY79), was used for the data analysis.Odds ratios were used to measure the risk of work-related injury in different worker groups.Results The findings showed that (i) construction workers started work earlier, worked longer days and fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 23 publications
(27 reference statements)
7
101
0
1
Order By: Relevance
“…When other variables are held constant, construction workers working for shorter duration had significantly lower work-related injuries. Similar results were reported by other studies, the risk of injury is associated with occupations of long working hours (Dong, 2005;Dong et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When other variables are held constant, construction workers working for shorter duration had significantly lower work-related injuries. Similar results were reported by other studies, the risk of injury is associated with occupations of long working hours (Dong, 2005;Dong et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The impact of occupational health and safety hazards faced by construction workers in developing countries is 10 to 20 times higher than those in Industrialized countries (Dong, 2005). The poor occupational safety situation among construction workers in developing countries are because of unsafe working environments such as poor design of equipment and work stations; lack of personal protective equipment and inadequate training of workers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiologic evidence shows that both daily and weekly workhours are directly related to an increase in the rate of occupational accidents and injuries and that the relation is not dependent on age, gender, occupation, or the sector of industry (35)(36)(37). An analysis of aggregated data showed an exponential increase of accident risk from 8 up to 16 hours at work.…”
Section: Long Workhoursmentioning
confidence: 99%
“…Although epidemiologic studies indicate that overtime and extended workdays are associated with impaired health (29) and accidents (36)(37)(38), there is sparse evidence that a decrease in the average number of workhours improves health. Those who work overtime are often in a position with high demands, but also with high decision latitude (16)(17)(18).…”
Section: Regulation Of Overtime and Excessive Workhoursmentioning
confidence: 99%
“…Previous studies have described the negative impact on health of long working hours. Occupational injuries and accidents increase with long working hours 3,4) , as do the incidences of sleep disorders, depression, musculoskeletal diseases, and cardiovascular diseases 5−7) . Some studies have also reported that long working hours negatively affect heart rate, heart rate variability, and blood pressure.…”
mentioning
confidence: 99%